2008
DOI: 10.1111/j.1365-294x.2008.03881.x
|View full text |Cite
|
Sign up to set email alerts
|

Geological history and oceanography of the Indo‐Malay Archipelago shape the genetic population structure in the false clown anemonefish (Amphiprion ocellaris)

Abstract: Like many fishes on coral reefs, the false clown anemonefish, Amphiprion ocellaris, has a life history with two different phases: adults are strongly site attached, whereas larvae are planktonic. Therefore, the larvae have the potential to disperse, but the degree of dispersal potential depends primarily on the period of the larval stage, which is only 8-12 days in A. ocellaris. In this study, we investigated the genetic population structure and gene flow in A. ocellaris across the Indo-Malay Archipelago by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 75 publications
(152 reference statements)
9
75
0
1
Order By: Relevance
“…Most of the past research supports the Center of Origin hypothesis (Barber et al 2006, Williams 2007, Timm & Kochzius 2008, Nuryanto & Kochzius 2009). In contrast, relatively few cases substantiate the Center of Overlap (Teske et al 2005, Gaither et al 2011) and Center of Accumulation hypotheses (Wilson et al 2001, Drew & Barber 2009).…”
Section: Origin Of Pomacentrus Coelestismentioning
confidence: 83%
See 1 more Smart Citation
“…Most of the past research supports the Center of Origin hypothesis (Barber et al 2006, Williams 2007, Timm & Kochzius 2008, Nuryanto & Kochzius 2009). In contrast, relatively few cases substantiate the Center of Overlap (Teske et al 2005, Gaither et al 2011) and Center of Accumulation hypotheses (Wilson et al 2001, Drew & Barber 2009).…”
Section: Origin Of Pomacentrus Coelestismentioning
confidence: 83%
“…Most of the populations had high haplotype diversity and low nucleotide diversity, which might be attributed to a rapid expansion of the population after a period of low population density (Grant & Bowen 1998). This diversity pattern is commonly found in reef fishes which lose their habitat during glacial-induced sea level fluctuations (Domingues et al 2006, Liu et al 2008, Timm & Kochzius 2008, as has been proposed for fish populations in Cenderawasih Bay (Allen & Erdmann 2006, Allen 2008. However, Cende rawasih Bay was the only population har boring extremely low haplotype (0.1538 ± 0.1261) and nucleotide (0.0005 ± 0.0008) diversity, indicating that the population may have suffered a recent bottleneck or founder event (Grant & Bowen 1998).…”
Section: Genetic Diversitymentioning
confidence: 90%
“…The A. ocellaris datasets were supplemented with CR sequences from previously published studies (Timm and Kochzius, 2008;Timm et al, 2012). FIGURE 1 | Sample sites for the clown anemonefish, Amphiprion ocellaris, (red circles) and the solitary sea squirt, Polycarpa aurata, (green circles) with corresponding sample sizes for each location in Spermonde Archipelago, Indonesia.…”
Section: Genetic Markers and Pcrmentioning
confidence: 99%
“…Despite medium to high genetic diversity (Timm and Kochzius, 2008;Timm et al, 2012;Dohna et al, 2015) currently measured at many sites, exploitation and destructive fishing practices continue to impact the reefs of Spermonde and may further decrease genetic diversity. The effect may be particularly strong in the southern area of the archipelago, close to the shore, where access and exploitation are already high and genetic evidence suggests localized reduction in diversity.…”
Section: Amphiprion Ocellarismentioning
confidence: 99%
“…E-mail: wbongkot@gmail.com This lack of connectivity can be seen in the genetic differentiation of many organisms, for example, coral (Clifton, 1997;Knittweis et al, 2009), macroalgae (Maggs & Callow, 2002), crustaceans (de Bruyn et al, 2005;Obst et al, 2012) and plants (Liao et al, 2009). Moreover, molecular genetic analyses of anemone fish (Timm & Kochzius, 2008), seastars (Yasuda et al, 2009) and coral (Knittweis et al, 2009) have found a clear genetic break between Indian and Pacific Ocean populations, which has been attributed to the ocean current patterns in the region.…”
Section: Introductionmentioning
confidence: 99%